Marketing Channel Strategies of Drug Trafficking Rats in Indonesia - Zakki, Nurdody; Ghufrony, Ahmad; Wibisono, Aryo; Kurdi, Moh. (PT. Riset Press International, 2024)
The dark market distribution channels for drug trafficking have become a chronic problem and a promising market in Indonesia. This circulation has reached remote villages and hamlets, regardless of individuals' identities or social statuses, making them potential quick recipients of narcotics. The National Narcotics Agency (BNN) states that preventing its distribution is more challenging than dealing with the culprits who use drugs. This research utilizes a systemic investigation method designed to understand the strategies of the dark market distribution channels for drug trafficking in Indonesia, employing a qualitative approach. For the current study, the researcher will commence the investigation in the Sumenep Regency, focusing on the location of the Sumenep Regency Penitentiary (LAPAS). The informants interviewed for the required data include detainees with drug abuse cases, former drug users and traffickers, the narcotics unit of the Sumenep Police Resort (Polres), the BNN of Sumenep Regency, and other informants believed to have knowledge about the dark market distribution channels for drugs in Indonesia. From the conducted research, it can be explained that the distribution of drug marketing does not use existing e-commerce platforms but relies on direct marketing to consumers or patients. Meanwhile, the marketing distribution extends through Surabaya, Bangkalan, Sampang, Pamekasan, and even from Kalimantan and Malaysia. As for the island regions of Banyuwangi and Bali, the distribution is also part of the marketing channels.